IMPLEMENTASI CONVENTION ON THE ELIMINATION OF ALL FORMS OF DISCRIMINATION AGAINST WOMEN (CEDAW) DALAM PENANGANAN KASUS FEMINISIDA DI MEKSIKO - Tay, Cherrie; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This study analyzes the challenges faced by Mexico in attempting to implement the principles of CEDAW in addressing feminicide cases. One of the earliest cases that drew significant international attention was the mass disappearance and murder of women in Ciudad Juárez in 1993. Since then, Mexico has continued to experience a high number of feminicide cases each year. Through CEDAW principles, Mexico has established a series of regulations and institutions to address feminicide and violence against women. This research employs a qualitative method and data collection techniques. It adopts a constructivist perspective and the norm life cycle theory. The findings indicate that Mexico remains at the norm cascade stage and struggles to reach the norm internalization stage due to a series of inhibiting challenges. The first challenge lies in the legal aspect, including the federal structure of the Mexican state, the difficulty in proving the elements of feminicide in individual cases, and the persistently high rates of impunity each year (exceeding 80–90% between 2020 and 2024). Socio-cultural challenges stem from the deeply rooted machismo culture in Mexico. Political challenges include the presence of necropolitics, narcopolitics, and the leadership of President AMLO, whose tendencies are often considered misogynistic. Lastly, economic challenges arise as millions of Mexican women choose to work in the informal sector despite being aware of its high risks. Keywords: Feminicide, Gender-Based Violence, CEDAW, Human Rights.